2015
DOI: 10.1108/jeim-07-2014-0077
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between attitude toward using and customer satisfaction with mobile application services

Abstract: Purpose – The methodology of mobile commerce as a significant application for both enterprises and customers are becoming crucial, but few studies discuss the usage attitude toward and customer satisfaction with mobile application (app) services in the life insurance industry. The purpose of this paper is to investigate the effects of attitude toward using life insurers’ mobile app services on customer satisfaction. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
78
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 47 publications
16
78
0
5
Order By: Relevance
“…This result is consistent with previous research that has confirmed a positive relationship between attitude and satisfaction (Chan et al, 2010). More recently, C-Y Lee et al (2015) found that consumers of an insurance application were more satisfied with the application service when their evaluation of that application was higher. They concluded that attitude toward using a technology positively influences customer satisfaction.…”
Section: H9asupporting
confidence: 82%
See 1 more Smart Citation
“…This result is consistent with previous research that has confirmed a positive relationship between attitude and satisfaction (Chan et al, 2010). More recently, C-Y Lee et al (2015) found that consumers of an insurance application were more satisfied with the application service when their evaluation of that application was higher. They concluded that attitude toward using a technology positively influences customer satisfaction.…”
Section: H9asupporting
confidence: 82%
“…Indeed, we think that satisfaction of the course is a student result that may be better for students who have a good attitude toward using a technology in the course. C-Y Lee et al (2015) suggested that users' attitude significantly and positively influences customer satisfaction of using life insurers' app services. Therefore, we propose to test the hypothesis below:…”
Section: Agementioning
confidence: 99%
“…As a result, pushed by the final aim of reaching new market competitive advantages (Porter and Heppelmann, 2014), they risk obtaining less profit than expected (Gebauer et al, 2005). Indeed, they attempt to increase their actual capabilities: to proactively manage lifecycle data (Gandhi et al, 2014), to provide customers with solutions better meeting their needs (Tan et al, 2010) and also to obtain back customer feedback and usage data to effectively (re)design and deliver new solutions on the market (Ponsignon et al, 2015). In this new context, the necessity to integrate and manage multiple sources of knowledge along the PSS design process in a systematic and structured way to allow an innovative design of PSS has been emphasised in the literature (Brissaud and Tichkiewftch, 2003) (Trevisan and Brissaud, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study extends our previous work [22], which explores the acceptance of mobile services, by focusing on the emotional aspect. The emotional impact on mobile services acceptance is observed in different extent, where the emotional aspect is the focus of the research [23,24] or it is presented only via the observed factors [25,26]. Also the emotions are observed in relation to the intention to adopt mobile services [23,27], continued use intention [24], or postacceptance behaviour [28].…”
Section: Introductionmentioning
confidence: 99%